When a dream turns into a nightmare: due to negative dream content or to negative appraisal? - Mathes, Jonas; Gieselmann, Annika; Pietrowsky, Reinhard (International journal of dream research, 2020)
Nightmares are a well-known phenomenon. The content of aversive dreams seems to be ubiquitous in dreams. Nevertheless, a dream containing aversive contents does not necessarily have to be a nightmare. We hypothesize that nightmares are rather caused by a more negative appraisal of the contents of aversive dreams than by the dream content itself. To investigate this question, N = 99 participants kept dream diaries over 28 consecutive days. An experimental group included persons with frequent nightmares and a control group of persons without nightmares. Violent dream content and emotions during the dream were analyzed by the dreamers themselves and as well as by four external raters. Regarding violent dream content in non-nightmare dream reports, the external raters usually agreed with the dreamers’ ratings. However, there was significant disagreement regarding the nightmare reports. Furthermore, external raters significantly rated the dreams as less positive than the dreamers did, and external raters rated the nightmare reports as more negative than the dreamers themselves did. Taken together, the results support the hypothesis that the classification of a dream as a nightmare does not only depend on its content but also on other factors. This suggests that the dreamers’ ratings of a dream as a nightmare are based on more factors than dream content.